Minimisation of exergetic cost of steam pipeline insulation (2020)
This paper presents the optimization study of steam pipeline insulation with three insulation materials: EPS, XPS and rockwool. The steam pipelines considered were single straight pipe, two-branch and three-branch networks with effects of pipe length and multilayered insulation on exergy loss, thickness and its attendant cost of insulation. Scaled exergetic cost model was developed and minimized to determine the optimum insulation thickness for pipeline carrying steam at inlet temperature of 200°C. For the same thickness of layer in composite insulation, preliminary analysis indicated that the best order of arrangement from the pipe outside surface is XPS-EPS-Rockwool. The optimum thickness of insulation and associated cost decreased with increase in flow rate of the steam but they increased with the pipe length. For different pipe lengths, the multilayer composite gave fairly smaller optimum insulation thicknesses and costs as compared with monolithic insulation of pipe with each of the insulation materials. The study also showed that each pipe in the multiple pipe networks had its own peculiar optimum thickness for each insulation layer in the multilayered composite to ensure pipe-end thermal quality of the steam pipeline.